Statistical Aspects of Community Health and Nutrition - Pandey, Chandra M (Indian Journal of Community Health, 2020)
One of the most common problems with the area of health and nutritional research is the limited number of quality books available that can provide research methodology, health indicators and their trend in a single volume. Statistical Aspects of Community Health and Nutrition is a one of the problem-based text book which completely fulfils the gap and stands to our expectations. This book is a single but comprehensive resource on maternal and infant mortality, anemia especially in adolescents and women in reproductive age group and, their causes, prevention, evaluation and validation methods including 30 clusters design, logistic regression and findings of recent relevant studies. Despite above, author also discusses the food insecurity and hunger, tuberculosis, influenza like prevalent diseases, their hotspot and available estimates, techniques for analyzing multiple response data, and small area estimation.